Starch-derived bioplastics: pioneering sustainable solutions for industrial use - Sobeih, Mahmoud Omar; Sawalha, Shadi; Hamed, Rinad; Ali, Fathilah; Kim, Minsoo P. (MDPI, 2025)
The use of plastics has increased due to the increase in population and applications in various industries. However, fossil fuel-based plastics have caused environmental issues and health hazards due to their non-degradable behavior. To resolve the on-going crisis of these non-degradable polymers, biopolymers have been considered as potential substitutes. Starch is being researched as a polymer matrix to develop bioplastics. Starch is abundant, but due to its poor water barrier and mechanical properties, other materials need to be incorporated in the matrix to improve the material properties. Natural fillers, plasticizers, essential oils, nanoparticles, or polymer blends are materials that can be used in starch-based bioplastics. Adding these materials enhances the mechanical and barrier properties. This review summarizes the recent developments in starch-based bioplastics and biocomposites and discusses the types of starch used, fillers, essential oils, and nanoparticles, explaining how they improve the mechanical, barrier, antibacterial, and biodegradability properties. Furthermore, many of the research products show potential to be used in industrial applications like packaging and agriculture. This review also discusses the potential of starch bioplastics in industrial applications like packaging, automotive applications, biomedical applications, electronics, construction, textiles, and consumer goods. This review also discusses the environmental impact of starch-derived bioplastic products, the life cycle, biodegradation, and recycling process. The circular economy of bioplastics, the economic feasibility of large-scale products, and regulation were also discussed, along with their challenges and the future perspectives of starch-based bioplastics.